Dimensions of the company’s efficiency - MANOLESCU, Gheorghe; GEAMĂNU, Marinela (Annals of Spiru Haret University. Economic Series, 2010)
The synthetic concept of business activity assessment, effectiveness circumscribe their theoretical and practical, a multi-dimensional configuration, which gives supportive and evaluative irrelevant in the field of business. In this sense, can be highlighted five dimensional coordinates business efficiency, coordinated, from different perspectives, trying to capture the synergy of effort and effect involved in the definition of efficiency. Multidimensional approach in four dimensions will be formalized through an array of dimensional coordinates of efficiency, which would allow revealing co-determinations of the defining elements of efficiency, both of those characteristics, their effort and effect, and synthesis of the characteristic of interaction between them. Business efficiency, in its essence and wholeness, integrative evaluative dimension is placed in a network of co-determination and interactions, at least, highlighted dimensional coordinates, measure the effectiveness and could only be realized through a system of interrelated indicators, each revealing a dimensional aspects relevant in a given evaluative context.